On the Concept of Civil Legal Liability in Russian Legal Science: A Critical Analysis - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2022)
This scientific article deals with the problem of the concept of civilliability. The latter is often misinterpreted by theoreticians and civilists. We believe that this is largely due to the unreasonable identification of legal liability measures and protection measures (restorative measures). The paper presents the author’s view of this problem.